An Observational Study of Retail Pharmacy Naloxone Prescriptions: Differences Across Provider Specialties and Patient Populations - Smart, Rosanna (J Gen Intern Med, 2019)
BACKGROUND: Despite exponential growth in pharmacy-dispensed naloxone, little information is available regarding variation in naloxone prescribing pattern across specialty groups, regions, and patient populations. OBJECTIVE: Explore variation in pharmacy-dispensed naloxone by prescriber specialty and patient characteristics. DESIGN: Cross-sectional analysis of the 2016 national retail pharmacy naloxone prescription claims from the IQVIA Real Longitudinal Prescriptions database. PARTICIPANTS: Naloxone prescribers and individuals filling naloxone prescriptions. MAIN MEASURES: Descriptive statistics assess differences across prescriber specialty groups in number of naloxone prescribers, patient and prescription characteristics, and geographic variation in naloxone dispensation and naloxone market share across prescriber specialty groups or formulation. KEY RESULTS: In 2016, 100,958 naloxone prescriptions written by 14,026 prescribers were filled by 88,735 patients. Primary care physicians accounted for the largest share of naloxone prescribers (45.9%); pain and anesthesia physicians and non-physicians prescribed to significantly greater numbers of patients (means of 10 and 8, respectively). While responsible for a relatively small share of naloxone dispensed (6.1%), psychiatrists and addiction specialists disproportionately served younger individuals, accounting for 49.5% of all prescriptions for individuals aged 35 and younger. Naloxone fill rates differed greatly across geographic regions, with the highest per capita rates in New England and the most concentrated prescribing in the West South Central and South Atlantic regions, where naloxone prescribers had the highest average numbers of patients (9.7 and 7.9, respectively). The South Atlantic and West South Central also had naloxone markets dominated by the Evzio® auto-injector, responsible for 50.3% and 43.8% of all naloxone dispensed in the regions; in contrast, New England’s naloxone market was predominantly comprised of generic formulations (48.8%) and Narcan® nasal spray (45.4%). CONCLUSIONS: Our findings reflect a need to better understand barriers to uptake of naloxone prescribing behavior among physicians and other prescribers to ensure individuals have adequate opportunity to receive naloxone from their treating clinicians. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s11606-019-05448-y) contains supplementary material, which is available to authorized users.